Comparison of interdental papilla around single implants in the anterior maxilla between two implant systems: A cohort study - Masoumeh Khoshhal; Fariborz Vafaei; Mahsa Najafi; Masoumeh Nikkhah (Tabriz University of Medical Sciences, 2018)
Background. In successful replacement of a tooth with a dental implant, soft tissue esthetic is as important as stability and function of the implant. Quality and quantity of the peri-implant mucosa can influence esthetic outcomes. This study assessed implant esthetic success of two different implant systems. In this regard the interdental papilla was evaluated and the relationship between implant type and crestal bone loss adjacent to implant was assessed. Methods. Eighteen patients (11 males, 7 females) with a total of 18 implants participated in this historical cohort study. Patients were divided into two groups based on the type of implants: Implantium group and SPI group; 36 interproximal papillae were evaluated photographically, using Jemt's papillary presence index (PPI). Radiographic analysis was carried out to find out the relation between bone loss and type of implant. Analysis of data was performed with SPSS 18, using Fisher's exact test, independent t-test, Spearman's correlation coefficient and ANOVA. Results. Comparison of photographs did not show a statistically significant difference in PPI between the two groups (P=0.94). Radiographic evaluation of crestal bone loss adjacent to implant shoulder did not reveal significant differences between the two groups (P=0.30). Conclusion. Implant therapy in the anterior maxilla, using Implantium or SPI system, did not result in significant differences in esthetics. In this study, there was an inverse relationship between the distance of contact point to bone crest and papilla index (P=0.002 in the SPI group) (P=0.02 in the Implantium group).